The Performance evaluation of 30kW class OWC wave power plant integrated with breakwater (Proceedings of the European Wave and Tidal Energy Conference, 2023)
In 2016, Korea started to develop a 30kW class wave power plant connected to a breakwater. After designing, manufacturing and performance testing of each energy conversion device, a demonstration plant was installed in Mukri Port, Jeju Island, Korea in 2021. After passing the completion inspection of the power generation facility, a full-scale grid-connected trial operation began in October 2021. The power plant consists of a sloped Oscillating Water Column, impulse air turbine, permanent magnet synchronous generator, AC-DC converter, energy storage system and integrated control system.This study introduces the performance evaluation results based on real sea operation data. The performance evaluation of the wave power plant under various wave height and period conditions was performed to evaluate the output power and efficiency of each bin. In addition, performance evaluations were conducted according to wave direction and tidal conditions to examine the effects. The correlation coefficient was derived by analyzing the correlation between wave height, period, wave directions, tide level and output power.